2020
DOI: 10.3389/fmicb.2020.608763
|View full text |Cite
|
Sign up to set email alerts
|

Transmission, Tropism, and Biological Impacts of Torix Rickettsia in the Common Bed Bug Cimex lectularius (Hemiptera: Cimicidae)

Abstract: The torix group of Rickettsia have been recorded from a wide assemblage of invertebrates, but details of transmission and biological impacts on the host have rarely been established. The common bed bug (Cimex lectularius) is a hemipteran insect which lives as an obligatory hematophagous pest of humans and is host to a primary Wolbachia symbiont and two facultative symbionts, a BEV-like symbiont, and a torix group Rickettsia. In this study, we first note the presence of a single Rickettsia strain in multiple la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…Based on the presence of RickB1 signals and the absence of corresponding NONEUB localization, it is likely that these points represent Rickettsia within the tardigrade. The shape, size, and pattern of distribution of the putative Rickettsia in our specimen are indeed similar to those of Rickettsia observed in FISH experiments of other ecdysozoans (Perotti et al, 2006;Pilgrim et al, 2020;Thongprem et al, 2021;Thongprem et al, 2020). This further supports the conclusion that we successfully detected Rickettsia in tardigrade tissues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the presence of RickB1 signals and the absence of corresponding NONEUB localization, it is likely that these points represent Rickettsia within the tardigrade. The shape, size, and pattern of distribution of the putative Rickettsia in our specimen are indeed similar to those of Rickettsia observed in FISH experiments of other ecdysozoans (Perotti et al, 2006;Pilgrim et al, 2020;Thongprem et al, 2021;Thongprem et al, 2020). This further supports the conclusion that we successfully detected Rickettsia in tardigrade tissues.…”
Section: Discussionsupporting
confidence: 90%
“…This further supports the conclusion that we successfully detected Rickettsia in tardigrade tissues. Although the use of a Rickettsia-specific probe alone can detect Rickettsia in ecdysozoans (Caspi-Fluger et al, 2012;Gottlieb et al, 2006;Kliot et al, 2014;Thongprem et al, 2021;Thongprem et al, 2020), future experiments using a three probe labeling scheme of RickB1 and NONEUB with the addition of EUB338 as a positive control would be useful to confirm our conclusion that Rickettsia is present in tardigrades. Because we analyzed tardigrades from the samples with the highest abundance of OTU 180 (classified as Rickettsia) from our previous study (Tibbs-Cortes et al, 2022), it is possible that the putative Rickettsia observed in our specimen is the same as OTU 180.…”
Section: Discussionsupporting
confidence: 56%
“…Cimex lectularius were acquired from the 'S1' isofemale colony maintained at the University of Bayreuth described in Thongprem et al (2020). Culicoides impunctatus females were collected from a wild population in Kinlochleven,Scotland (56° 42' 50.7''N 4° 57' 34.9''W) on the evenings of the 2nd and 3rd September 2020 by aspiration.…”
Section: Sample Collection For Targeted Genome Assemblymentioning
confidence: 99%
“…Torix clade Rickettsia are known to be heritable symbionts, but their impact on host biology is poorly understood, despite the economic and medical importance of several hosts (inc. bed bugs, black flies, and biting midges). Rare studies have described the potential effects on the host, which include: larger body size in leeches (Kikuchi & Fukatsu, 2005); a small negative effect on growth rate and reproduction in bed bugs (Thongprem et al, 2020); and an association with parthenogenesis in Empoasca Leafhoppers (Aguin-Pombo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The primary endosymbionts (such as Portiera aleyrodidarum in whiteflies) can supply essential nutrients under limited or unbalanced hosts’ diets thus essential for host survival ( Douglas, 1998 ; Baumann, 2005 ). Secondary endosymbionts on the other hand are not essential for host survival; however, recent studies have revealed that they play other important roles in ecological and evolutionary phenomena, such as manipulating reproduction of their hosts ( Segoli et al., 2013 ; Baldini et al., 2014 ; Staudacher et al., 2017 ; Thongprem et al., 2020 ; Wang et al., 2020 ; Candasamy et al., 2022 ; Li et al., 2022 ). Normally, many arthropod individuals harbor more than one species of endosymbionts, and they are mainly inherited vertically from mother to offspring with high fidelity, which is higher than 99.0% homology between the generations ( Karut et al., 2020 ; Shan et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%